PATTERN OF INDUSTRY PRACTICES IN EFFORTS TO PREPARE VOCATIONAL TEACHERS COMPETENCES IN ELECTRICAL SKILLS - Ratnata, I. W.; Sumarto, Sumarto; Djohar, A. (INVOTEC, 2018)
This research is based on by issues developing, that graduates of vocational teacher education have not yet had adequate vocational competence according to demand the world of work, primarily as vocational teachers in the field of electrical practices. Industry practice constitutes vehicle for students in order to have vocational competence according to the need the world of industry. This research using qualitative approach, in which data is collected from some industries in Bandung. It is found that patterns of industry practices done in the world of education have not yet run properly according to demand as vocational teacher even the world of work. Therefore through this research is drawn up the design of an patterns of industry practices that can maximize the activities of student for doing industry practice especially for electrical field. Conclusions, where pattern of industry practices using approaches the partnership cooperation with involving government, the world of industry, and university, can run properly and students have good skills and competence according to their field of electrical skills.